Die konsep "Seun van God" in Grieks-Romeinse en Hellenisties-Semitiese literatuur - Aarde, Andries van (Hervormde teologiese studies, 1997)
The notion 'Son of God' in Graeco-Roman and Hellenistic-Semitic literature. Christians among the Greek-speaking Israelites referred to Jesus as, inter alia, 'Son of God'. The connotation of this honorific title differs from the usage of that by Israelites prior to Hellenistic influence, who in the First Testament referred to their messianic king as 'Son of God'. The new connotation was, to a Hellenistic audience, a commonality. According to Rudolf Bultmann it was 'gemeingriechische Denke '. The article aims at identifying three different types of the notion 'Son of God' in Graeco-Roman and Hellenistic-Semitic literature: the divine human as miracle worker, the pre-existent God-like figure who is paradoxically associated with human fate, and the cosmological figure who is identified as God's Wisdom. It is shown that all three types occur in the Second Testament as interpretations of the soteriological meaning of Jesus' birth and death.